2018
DOI: 10.1111/pce.13331
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of native oak to recurrent drought conditions simulating predicted climatic changes in the Mediterranean region

Abstract: The capacity of a Quercus pubescens forest to resist recurrent drought was assessed on an in situ experimental platform through the measurement of a large set of traits (ecophysiological and metabolic) studied under natural drought (ND) and amplified drought (AD) induced by partial rain exclusion. This study was performed during the third and fourth years of AD, which correspond to conditions of moderate AD in 2014 and harsher AD in 2015, respectively. Although water potential (Ψ) and net photosynthesis (Pn) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 68 publications
4
31
2
1
Order By: Relevance
“…During fumigation, saplings were enclosed in two dynamics chambers of 77 L volume (77 cm height, 35 cm diameter) and PTFE-made (Polytetrafluoroethylene), based on our previous models [17,22,23] ( Figure 5) (Figure 5a,b). Each chamber was enclosed using a Nalophan film (MediSense, UK).…”
Section: Acer Monspessulanum Fumigation Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…During fumigation, saplings were enclosed in two dynamics chambers of 77 L volume (77 cm height, 35 cm diameter) and PTFE-made (Polytetrafluoroethylene), based on our previous models [17,22,23] ( Figure 5) (Figure 5a,b). Each chamber was enclosed using a Nalophan film (MediSense, UK).…”
Section: Acer Monspessulanum Fumigation Treatmentsmentioning
confidence: 99%
“…In Mediterranean forests, two tree species, Acer monspessulanum L. and Quercus pubescens Wild., coexist together in mature forests with a remarkable tree density in some forests [17] implying that their canopies are intertwined. Both species are also known for their remarkable resistance to drought [22,23] while they feature contrasting capacities to emit isoprene. A. monspessulanum releases negligible isoprene emission rates (0.3 µg.g −1 .h −1 ) or any other terpene [17], while Q. pubescens is the major isoprene emitter in the Mediterranean region (~100 µg.g -1 .h −1 ) [24].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study carried out on the site of O 3 HP, a two-fold increase in stomata closure was found in spring from Q. pubescens of the rain exclusion treatment as compared to the control plot [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Summer stomatal conductance was significantly reduced to 56% in control as compared to the rain exclusion plot with a concomitant reduction of net photosynthesis [ 29 ]. Hence, it is probable that the decrease in phosphate ion transmembrane transporter activity reflects a balance of the redox state between photosynthesis light reactions and the Calvin cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The variable responses reported previously emphasize that BVOC emissions under drought are highly dependent on tree species (sensitivity) as well as the intensity and temporal extend of the stress events (Dani et al, 2015). Different effects are thus explained by species sensitivity as well as drought intensity (Niinemets, 2010;Klein, 2014;Saunier et al, 2018). For example, the same species can possess an increase of isoprene emissions under mild drought while severe drought decreases emissions (Brilli et al, 2007;Genard-Zielinski et al, 2014;Dani et al, 2015).…”
Section: Plant Water Statusmentioning
confidence: 91%